Construction risk in river and estuary engineering a guidance manual - Morris, Mark, 1965 June 26-; Simm, Jonathan (Thomas Telford, 2000)
The river and estuary environment pose a range of new and increased risks to the engineer. To complete works successfully the engineer needs to manage these risks such that construction is done safely and to specification, and this book provides guidance in risk assessment and management techniques.